The Aesthetic quality assessment of the landscape around Cibinong Botanic Garden's lake as a reference for development based on landscape visual aesthetics - Asnidar, Yuni; Noviandi, Tri Utomo Zelan (Buletin Kebun Raya, 2024)
Cibinong Botanic Garden has natural potential views that can be managed in several areas, however, this potential has yet to be fully optimized. One of the key highlights for tourists visiting the garden is an artificial lake, which has the potential for natural landscape views. The area surrounding the lake can be developed, but, a development priority reference is needed by looking at all aspects, one of which is the aesthetic aspect of the landscape. This study aimed to determine the aesthetic potential of the landscape around Cibinong Botanic Garden’s Lake based on user perceptions and preferences. The landscape aesthetic quality is measured by assessing the views within the site from the perspective of the user who understands the landscape aesthetic aspects. The initial method is to determine vantage points with landscape aesthetic potentials to be assessed based on the perceptions and preferences of the target respondents and analyzed using Scenic Beauty Estimation (SBE) to choose the classes of landscape aesthetic quality. The results are divided into two categories of aesthetic quality: ten landscape views with high landscape aesthetic quality and five with moderate landscape aesthetic quality. High landscape aesthetic quality describes high-potential value areas that could be developed following the functions of a botanic garden by maintaining and emphasizing the landscape's visual quality. Meanwhile, the moderate landscape aesthetic quality could be developed into an area that supports the function of botanic gardens with efforts to improve the landscape's visual quality.